2014
DOI: 10.1093/jpepsy/jsu068
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Construct of Fear of Hypoglycemia in Pediatric Type 1 Diabetes

Abstract: These constructs provide a more comprehensive understanding of pediatric FoH and have implications for interventions aimed at reducing FoH in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 29 publications
6
56
0
5
Order By: Relevance
“…In contrast to a previous study 5, but consistent with several other studies 4, 6, 7, 8, 9, 10, 11, 12, 13, HbA 1c was not related to parental fear of hypoglycaemia. HbA 1c was assessed by parental report, and therefore may not be reliable.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In contrast to a previous study 5, but consistent with several other studies 4, 6, 7, 8, 9, 10, 11, 12, 13, HbA 1c was not related to parental fear of hypoglycaemia. HbA 1c was assessed by parental report, and therefore may not be reliable.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in line with studies that classifed severe hypoglycaemia as a hypoglycaemic event resulting in seizure, unconsciousness or hospital admission 5, 6, 8, 9, 11, 12, 13. Based on previous studies, the frequency of hypoglycaemia 5, 12 and hypoglycaemic events at school 8 seem to be more important factors in relation to parental fear of hypoglycaemia than severe hypoglycaemia.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, in a recent study with parents and adolescents with T1D, researchers identified a two-factor structure within the HFS behavior subscale corresponding to potentially adaptive (e.g., ''Avoid being alone when blood glucose could drop'') versus maladaptive (e.g., ''Try to run blood sugars a little high to be safe'') behaviors. 20 Although we did not directly test for these subfactors in our analyses, items 2, 5, and 9 do reflect potentially adaptive behaviors to prevent low blood glucose, which may explain why they did not load on a factor that also included potentially maladaptive behaviors. Thus, as a future study, it may be important to confirm if a two-subfactor structure exists for the HFS-PYC behavior scale in a larger sample of parents.…”
Section: Discussionmentioning
confidence: 99%